Depression, Anxiety and Stress Levels During Covid-19 Pandemic among Frontliners of IIUM Hospital and Kuantan-Campus, and its Associated Factors - Abdulllah, Fa'iza; A Rahman, Nor Azlina; Nik Ahmad , Nik Nur Fatnoon; Samsudin , Suhaiza; Ahmad Basri , Nadzirah; Md. Aris , Mohd Aznan; Mat Nor , Mohd Basri (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Psychological burden of frontliners increased during the COVID-19 pandemic, leading to psychiatric illnesses reducing productivity. Assessing their mental health status is vital in providing effective care. Our aim was to investigate the levels of depression, anxiety, stress, and associated factors among frontlines of International Islamic University Malaysia (IIUM), Sultan Ahmad Shah Medical Centre (SASMEC) and Kuantan-Campus during the recent COVID-19 pandemic. MATERIALS AND METHODS: Cross-sectional study among 261 SASMEC@IIUM and 125 Kuantan-campus IIUM frontliners from March 2021 to June 2022 using self administered validated DASS-21 questionnaire. Descriptive statistics, Chi-Square and Fisher’s Exact tests were used for data analysis. Frontliners with severe and very severe DASS scores were offered psychoeducational counselling for intervention. RESULTS: Out of 386 respondents, 82.1% were clinical frontliners, 65.8% were female, and 65.8% were married. The prevalence was 15.8%, 29.5% and 9.3% for depression, anxiety and stress, respectively. This study showed no statistical differences between the clinical and non-clinical, and between SASMEC@IIUM and Kuantan-campus frontliners on depression, anxiety and stress levels. Those with post-traumatic events had significant association with depression (p<0.001) and anxiety (p<0.001), while anxiety significantly associated with chronic diseases (p=0.034). CONCLUSION: Over one-fourth of frontline staff suffered from anxiety during the COVID-19 pandemic, whereas 9-15% experienced depression and stress. Frontliners with post-traumatic events or chronic diseases required additional support in coping with their mental health burden. No significant difference was found in anxiety, depression and stress levels between clinical and non clinical or between hospital-based and on-campus frontliners, suggesting a comprehensive mental health screening and timely intervention to all frontliners regardless of their post or area of service.